Pasado y presente en Ricoeur y de Certeau. Algunas consideraciones - Lythgoe, Esteban (ARFIL y UNL, 2018)
This paper studies the way in which Ricoeur and de Certeau conceives the relationship between historical narration and past. Its hypothesis is that there has been a change in Ricoeur’s position between Time and Narrative and Memory, History and Oblivion. In the first book the articulation between historical narration and past is articulated by the plot. In the second one, the concept of event makes his analysis more similar to de Certeau's. We discuss Ricoeur’s critic to de Certeau in Time and Narrative and sustain that Memory, History and Oblivion, is not affected by this critic thanks to the concept of representation.